An Informal Approach to Interest-based Negotiations – Paul Anton Esterhazy and the “Cottage Coterie” - Katalin Schrek (Theatrum Historiae)
Paul Anton Esterhazy was a prominent figure of the Hungarian aristocracy and a leading AustroHungarian politician, as well as a highly qualified and internationally recognised diplomat, with an extensive network of personal relations within the British elite. Esterhazy was an ambassador of Austria to London from 1815 to 1842 and represented the interests of the Central European state. In the mid-1820s he was a member of the so-called “Cottage Coterie”, a group created by King George IV and inspired by the aim of counterbalancing the political influence of the new secretary of the Foreign Office, George Canning. The meetings of the group were political and social events as well. Esterhazy was connected with close (family and political) ties to George IV, and thus he was a well trusted person in the royal court. My paper focuses on the activity and role of Esterhazy within the Cottage Coterie.